Analisis Performa, Overload dan Kerentanan Pada Website Basarnas Bengkulu Untuk Optimalisasi Kinerja - Cheka, Julyane Kevin; Toyib, Rozali; Wijaya, Ardi; Muntahanah (LPPM Universitas Dinamika Bangsa, 2025)
The Bengkulu Basarnas website plays a crucial role in providing information related to search and rescue activities to the public. However, with the increasing number of visitors and the need for fast and accurate information, the site faces several challenges related to performance, overload, and vulnerabilities such as slow page load times, a website that tends to be unresponsive, and indications of defacement, which are certainly detrimental. Therefore, research was conducted with the aim of analyzing and providing recommendations for optimizing website performance. Implementing the Software Testing Life Cycle (STLC) method, a method used for software testing, and assisted by tools such as PageSpeed Insights, Apache Jmeter, and Acunetix, enabled the research to be conducted comprehensively and efficiently. The results obtained an average performance score of 81.87, which is included in the good range but still needs improvement. On overload, the research results were obtained, namely scenario 1 with 5 users (105 samples) there was 0.00% error, scenario 2 with 15 users (315 samples) there was 0.32% error, and scenario 3 with 45 users (945 samples) there was 1.90% which overall shows that website performance is still quite good at low loads but decreases at high loads. And on vulnerabilities, the research results were in the Low severity vulnerabilities category, which means there are minor vulnerabilities and are still relatively safe but still need to be followed up for prevention efforts. Based on these findings, it is recommended to pay attention to server infrastructure, optimize content or images, and improve and pay attention to system security in order to minimize vulnerabilities to prevent threats and attacks that can disrupt website performance.